Detailed Studies of the Alkylation Sides of Pyridin‐2‐yl and 4, 6‐Dimethylpyrimidin‐2‐yl‐cyanamides. (28th March 2016) - Shestakov, Alexander S.; Moustafa, Amr H.; Bushmarinov, Ivan S.; Goloveshkin, Alexander S.; Shapovalov, Alexey V.; Shikhaliev, Khidmet S.; Prezent, Mikhail A.; Sidorenko, Oleg E.
Abstract : Pyridin‐2‐yl‐ and 4, 6‐dimethylpyrimidin‐2‐yl‐cyanamides entered into an alkylation reaction in the form of sodium salts. Pyridin‐2‐yl cyanamide2 was alkylated at endo‐nitrogen atom of pyridine ring, while 4, 6‐dimethylpyrimidin‐2‐yl cyanamide1 was effectively alkylated at exo‐nitrogen atom of amino cyanamide group. The alkylation of cyanamides1 and2 with phenacylbromide gave the corresponding acetophenone derivatives. As a result of their intramolecular cyclization reactions 3‐(4, 6‐dimethylpyrimidin‐2‐yl)‐5‐phenyloxazol‐2(3 H )‐imine in the case of cyanamide1 and 2‐amino‐3‐benzoylimidazo[1, 2‐ a ]pyridine in the case of cyanamide2 were formed. The alkylated derivatives of pyridin‐2‐ylcyanamide2 possess visible blue fluorescence with the main peak at 421 – 427 nm. Abstract :